Molecular Docking of Citronellol, Geraniol and Ester Derivatives as Pim 1 Kinase Inhibitor of Leukemia Cancer - Galuh Widiyarti; Firdayani Firdayani; Muhammad Hanafi; Soleh Kosela; Emil Budianto (Syarif Hidayatullah State Islamic University, 2019)
The proviral insertion site in Moloney murine leukemia virus-1 (Pim1) kinase is overexpressed in many human cancer diseases. Inhibition of Pim1 kinase has been reported can suppress cell proliferation and induce apoptotic cell death, so that the protein could be chosen as drug target for the treatment of cancer. Citronellol and geraniol mainly contained in citronella oil that’s one of Indonesian natural products have bioactivity as antitumor agents, so that both of the compounds can be used as guiding compound to be developed as chemoprevention and chemotherapeutic agent compounds for cancer especially for leukemia cancer. In this research, sixteen citronellol and geraniol esters as an inhibitor of leukemia cancer designed were docked based on their interaction with leukemia receptor target of Pim1 kinase by using Molegro Virtual Docker (MVD). The result showed that the binding citronellol and geraniol esters to Pim1 kinase are more stable and better affinity than the binding between citronellol and geraniol, indicated by rerank score were lower than rerank score of citronellol/geraniolPim1 kinase. The docking resulted in the four top-ranked compounds, namely, citronellyl caproate, citronellyl caprylate, geranyl caproate and geranyl caprylate with rerank score value from -182.560 to -189.822 KJ/mol. These compounds have hydrogen bonding with amino acid residues of Lys 67 and Asp 186 of an active site of Pim1 kinase. Based on Lipinski’s rule of five, among of the four top-ranked compounds, citronellyl caproate and geranyl caproate were predicted have potency as new chemopreventive and chemotherapeutic agents for leukemia anticancer candidates.